A zeolite modified carbon paste electrode based on copper exchanged clinoptilolite nanoparticles for voltammetric determination of metronidazole. Issue 23 (3rd March 2017) - Shahnazari-Shahrezaie, Elahe; Nezamzadeh-Ejhieh, Alireza
Abstract : Modified carbonpaste elelctrode with Cu(ii )-exchanged clinoptilolite nanoparticles showed increased peak current in the presence of metronidazole. Abstract : A simple and effective zeolite modified electrode (ZME) was constructed from Cu(ii )-exchanged clinoptilolite nanoparticles (Cu(ii )-CNP). The modifier was characterized by FTIR, BET, XRD and TEM techniques. The modified carbon paste electrode (Cu(ii )-CNP/CPE) was used for the voltammetric determination of metronidazole (MNZ). The best voltammetric response was obtained by the electrode containing 20% of the modifier in NaCl 0.4 mol L −1 at pH 6. The electrode showed a linear response in the concentration range of 2.0 × 10 −8 to 1.6 × 10 −6 mol L −1 MNZ with a detection limit of 4.1 × 10 −9 mol L −1 from square wave voltammetry. The electrode showed good repeatability, reproducibility, and a long lifetime based on statistical tests. The electrode also has good selectivity and good applicability in the determination of MNZ in some pharmaceutical samples.